Imaging of neuroinflammation in migraine with aura: A [11C]PBR28 PET/MRI study. (23rd April 2019) - Albrecht, Daniel S.; Mainero, Caterina; Ichijo, Eri; Ward, Noreen; Granziera, Cristina; Zürcher, Nicole R.; Akeju, Oluwaseun; Bonnier, Guillaume; Price, Julie; Hooker, Jacob M.; Napadow, Vitaly; Loggia, Marco L.; et al.
Abstract : Objective: To determine if migraine with aura is associated with neuroinflammation, which has been suggested by preclinical models of cortical spreading depression (CSD) as well as imaging of human pain conditions. Methods: Thirteen migraineurs with aura and 16 healthy controls received integrated PET/MRI brain scans with [ 11 C]PBR28, a radioligand that binds to the 18 kDa translocator protein, a marker of glial activation. Standardized uptake value ratio (SUVR) was compared between groups, and regressed against clinical variables, using region of interest and whole-brain voxelwise analyses. Results: Compared to healthy controls, migraineurs demonstrated SUVR elevations in nociceptive processing areas (e.g., thalamus and primary/secondary somatosensory and insular cortices) as well as in areas previously shown to be involved in CSD generation (visual cortex). SUVR levels in frontoinsular cortex, primary/secondary somatosensory cortices, and basal ganglia were correlated with frequency of migraine attacks. Conclusions: These findings demonstrate that migraine with aura is associated with neuroimmune activation/neuroinflammation, and support a possible link between CSD and glial activation, previously observed in animals.